Isolation and Characterization of Halotolerant Plant Growth Promoting Rhizobacteria From Durum Wheat (Triticum turgidum subsp. durum) Cultivated in Saline Areas of the Dead Sea Region - Albdaiwi, Randa N.; Khyami-Horani, Hala; Ayad, Jamal Y.; Alananbeh, Kholoud M.; Al-Sayaydeh, Rabea (Frontiers in Microbiology, 2019)
Plant growth promoting rhizobacteria (PGPR) are beneficial microorganisms that can be utilized to improve plant responses against biotic and abiotic stresses. In this study, 74 halotolerant bacterial isolates were isolated from rhizosphere and endorhizosphere of durum wheat (Triticum turgidum subsp. durum) plants cultivated in saline environments in the Ghor region near the east of the Dead Sea. 16S rDNA partial sequences and phylogenetic analysis of 62 isolates showed clear clustering of the isolates into three phyla: Firmicutes (61.3%), Proteobacteria (29.0%) and Actinobacteria (9.7%). At the genus level, the majority of them were grouped within the Bacillus, Oceanobacillus and Halomonas genera. The isolates, which possessed plant growth promoting traits including nitrogen fixation, ACC deaminase activity, auxin production, inorganic phosphate solubilization and siderophore production, were selected. The effect of the inoculation of selected PGPR strains on growth of salt sensitive and salt tolerant durum wheat genotypes under high salt stress conditions was evaluated. Six halotolerant PGPR strains were able to improve survival in inoculated plants under high salinity stress conditions as reflected in higher germination percentages and seedling root growth when compared with non-inoculated plants. Furthermore, three halotolerant PGPR strains were able to improve durum wheat tolerance to water deficit stress. In addition, antagonistic effect in four halotolerant PGPR strains against an aggressive pathogenic isolate of Fusarium culmorum that causes crown rot disease was observed in a dual culture assay. In conclusion, the halotolerant PGPR strains described in this study might have great potential to improve durum wheat productivity under different stress conditions.